Compulsory preferential voting, social media and 'come-from-behind' electoral victories in Australia. Issue 1 (2nd January 2021) - Reilly, Benjamin; Stewart, Jack Hudson
ABSTRACT: What is the relationship between Australia's system of compulsory preferential voting and the ideological stance of elected members? Utilising a unique dataset of social media communication from the 2013 federal election, we show how preference flows influence parliamentarians' subsequent communications to voters. MPs who were behind on the first count but gained sufficient preferences to win a seat – whom we call 'come-from-behind' winners – adopted distinctively centrist communication strategies, occupying an ideological 'cross-over zone' between the most right-leaning Labor member and most left-leaning Coalition member. Most of these 'come-from-behind' winners today are Labor MPs, illustrating the changing partisan impact of compulsory preferential voting, from historically advantaging the conservative side of politics to now clearly benefitting Labor and, to a lesser extent, independent candidates.